The effects of external shocks on the business cycle in China: A structural change perspective - Michael Murach; Helmut Wagner (University of Hagen, Center for East Asia Macro-economic Studies (CEAMeS), 2019)
We study the effects of external shocks on the business cycle in China and its sectors (agriculture, industry, and services) in terms of real GDP growth using several small dimensional VAR models with Cholesky identification for the period 1996–2014. We show that China - in particular its industrial sector - is susceptible to shocks, which can be related to a trade channel, a financial channel, and a confidence channel of business cycle transmission from major trading partner countries to the Chinese economy. We extend the previous literature by explicitly focusing on response of the Chinese economy at the sectoral level and investigating the presence of confidence channels by analyzing the reaction in Chinese business and consumer confidence. If interpreted from the perspective of ongoing structural change and rebalancing in China, our findings can be interpreted as the result of a still very dominant industrial sector, and a previously export- and investment-driven growth model. Tertiarization in China could be one way of increasing the economy's future resilience to external shocks. However, the future structure of both the industrial and service sectors may be very decisive.
urn:nbn:de:hbz:708-dh10418
Keywords: F43; F44; C32; 330; International transmission channels; Transmission of shocks; Structural vector autoregression; Structural change